The United States and the universal periodic review of the UN Human Rights Council - De Carvalho Hernandez, Matheus [UNESP]; Da Rosa, William Torres Laureano [UNESP] (Pontificia Universidade Catolica de Minas Gerais, 2018)
The Universal Periodic Review is the newest institutional mechanism of monitoring human rights created by the UN together with the emergence of the Council in 2006. Through this mechanism, all UN member states have begun to have their human rights practices and policies analysed by their peers over a four-year cycle. The United States has always had a tense relationship with the Human Rights Council, especially during the Bush administration, which boycotted it financially, and currently under Trump. However, there is still little literature on the two review cycles the US passed, both under the Obama administration. In addition to the historical analysis that culminated in the US entry into the body after the end of the Bush administration, this article brings with it an unprecedented effort of comparative mapping of these two cycles. It systematizes from which countries the recommendations directed to the US come from, what are the issues and what are the US positions on these recommendations. The objective is to understand how this unprecedented mechanism operates and, mainly, the performance of the USA, in order to contribute to the opening of this research agenda.
Os EUA e a revisão periódica universal do Conselho de Direitos Humanos da ONU
Keywords: Human Rights Council; United States of America; Universal Periodic Review